1995
DOI: 10.1109/12.376173
|View full text |Cite
|
Sign up to set email alerts
|

Embedding graphs onto the Supercube

Abstract: In this paper we consider the Supercube, a new interconnection network derived from the hypercube introduced by Sen in 10]. The Supercube has the same diameter and connectivity of a hypercube but can be realized for any number of nodes not only for powers of 2.We study the capabilities of the Supercube to execute parallel programs using graph{embedding techniques. We show that complete binary trees and bidimensional meshes (with a side length power of 2) are spanning subgraphs of the Supercube. Then we prove t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…The existence of pancyclicity in a network is even more useful because it implies that the network can embed cycles with arbitrary length, and therefore, it has been extensively studied. Previous results showed that many interconnection networks are pancyclic, including de Bruijn networks [19,33], Xtrees [23], product-shuffle networks [24], alternating group graphs [18], and supercubes where the number of vertices is not a power of two [2]. Also, two-dimensional meshes [1], two-dimensional toroidal meshes [7], and hypercubes [12] have been shown to be even-pancyclic.…”
Section: Introductionmentioning
confidence: 98%
“…The existence of pancyclicity in a network is even more useful because it implies that the network can embed cycles with arbitrary length, and therefore, it has been extensively studied. Previous results showed that many interconnection networks are pancyclic, including de Bruijn networks [19,33], Xtrees [23], product-shuffle networks [24], alternating group graphs [18], and supercubes where the number of vertices is not a power of two [2]. Also, two-dimensional meshes [1], two-dimensional toroidal meshes [7], and hypercubes [12] have been shown to be even-pancyclic.…”
Section: Introductionmentioning
confidence: 98%
“…as guest graphs [5,9,11,13,15,18,20], because these interconnection networks are widely used in parallel computing systems.…”
Section: Introductionmentioning
confidence: 99%
“…as guest graphs [1][2][3][4]11,13,14,16,17], because these interconnection networks are widely used in parallel computing systems. Embeddings of paths, cycles, and trees into crossed cubes were studied in [3,6,10,11,14,16].…”
Section: Introductionmentioning
confidence: 99%